The Impact of Special Autonomy on the Convergence of Regional Economic Growth in Aceh, Indonesia - Teuku Zulham; Said Muhammad; Raja Masbar; Sirojuzilam . (Aceh International Journal of Social Science, 2015)
This study aims to assess the impact of special autonomy on the convergence of regional economic growth in Aceh, as well as factors that affect the convergence of economic growth before and after the enactment of special autonomy in Aceh. The independent variable in this study is the initial GDP per capita, working population, poor people, school duration, life expectancy, gross fixed capital formation, local revenue, equalization fund, and total receipts. The dependent variable is economic growth. The data used is secondary data in the form of panel data of the 23 districts / cities in Aceh from 1991 to 2012. The model used is panel data regression model which are grouped into two part of analysis which is before special autonomy (1991-2001) and after special autonomy (2002-2012). The estimation results indicate that there is sigma convergence of Aceh's regional economic growth which is shown by the decreasing value of standard deviation from 0.7698 before special autonomy to 0.5411 after special autonomy. In absolute terms, it is also ensued that there is a significant convergence of regional economic growth in Aceh in which the value of half-life of convergence to non-oil is about 27 years. While the speed of convergence after the special autonomy is increased. Conditionally, the exogenous variables that have a significant effect was only local revenues and school duration. Entire period takes 30 years half-life convergence with the speed of convergence on average 2.30 percent per year towards a steady state. The development program in the future should be oriented in creating many more employment opportunities, reducing poverty significantly, the enhancement of life expectancy, increasing people’s education to a higher level, as well as reducing the development gap in each district in Aceh. Keywords: Convergence, Speed of Convergence, Half-Life of Convergence, Special Autonomy, the Regional Economic Growth